2015
DOI: 10.1111/tri.12495
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the advantage of zero-HLA mismatches in unrelated living donor kidney transplantation: implications on kidney paired donation

Abstract: SummaryThe OPTN/UNOS Kidney Paired Donation (KPD) Pilot Program allocates priority to zero-HLA mismatches. However, in unrelated living donor kidney transplants (LDKT)-the same donor source in KPD-no study has shown whether zero-HLA mismatches provide any advantage over >0 HLA mismatches. We hypothesize that zero-HLA mismatches among unrelated LDKT do not benefit graft survival. This retrospective SRTR database study analyzed LDKT recipients from 1987 to 2012. Among unrelated LDKT, subjects with zero-HLA misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…A recent retrospective analysis matched 83 0-HLA mismatches to 407 controls with more than 0 HLA mismatches in living donors; the authors reported that 0-HLA mismatch did not confer improved death-censored graft survival and patient survival. 7 In another study, while HLA-DR mismatch was a risk factor for acute rejection, HLA mismatch did not increase the risk of allograft loss or patient death. 5 Moreover, the adjusted 5-year allograft survival rate for unrelated living kidney transplantation was similar to the haploidentical living donation.…”
mentioning
confidence: 93%
“…A recent retrospective analysis matched 83 0-HLA mismatches to 407 controls with more than 0 HLA mismatches in living donors; the authors reported that 0-HLA mismatch did not confer improved death-censored graft survival and patient survival. 7 In another study, while HLA-DR mismatch was a risk factor for acute rejection, HLA mismatch did not increase the risk of allograft loss or patient death. 5 Moreover, the adjusted 5-year allograft survival rate for unrelated living kidney transplantation was similar to the haploidentical living donation.…”
mentioning
confidence: 93%
“…Among all zero‐HLA mismatched living donor transplants, a significant benefit in death‐censored graft survival was seen in related (83%) over unrelated (78%) living donor transplant recipients. Finally, zero‐HLA mismatching was not associated with improved patient survival after living‐unrelated kidney transplantation .…”
mentioning
confidence: 87%
“…In this edition of Transplant International , Casey et al . report the results of their study on the effect of the degree of HLA matching on graft survival after living‐unrelated donor kidney transplantation. Using data from the OPTN Scientific Registry of Transplant Recipients, 109 987 recipients of a living donor kidney transplanted in the USA between 1 October 1987 and 4 September 2012 were identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schließlich stellt die verlängerte kalte Ischämiezeit (wie in der konventionellen Leichenspende häufig der Fall) einen relevanten Risikofaktor für das postoperative Auftreten einer verzögerten Funktionsaufnahme des Transplantats (Delayed Graft Function, DGF) wie auch für das Auftreten von akuten Abstoßungsepisoden dar [4,5]. Eine kürzlich durchgeführte Analyse hinsichtlich des Nutzens einer HLA-Kompatibilität zwischen Lebendspender und Organempfänger hat keinen Vorteil zum herkömmlichen Verfahren aufgezeigt [6].…”
Section: Einschätzung Des Immunologischen Risikos Vor Nierentransplanunclassified